Aeschylus’ Agamemnon 782-974: The poetics of deixis - Gasti, Helen (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2015)
In this paper I’ll try to demonstrate that it is possible, using a deictic approach, to reveal the traits of Agamemnon’s character in the third episode of Aeschylus’ Agamemnon (782-974). Deixis as a means of understanding Agamemnon’s portrayal in his first speech (810-854) refutes the widely held opinion among scholars of the hubris syndrome. Nevertheless from our analysis of the deictic network it follows that despite Agamemnon’s concern with political and religious propriety his egocentric inclination smolders in lines 914-930, expressed through the striking abundance of personal and possessive pronouns of the first person often at emphatic position of the verse. In conclusion deixis is proven to be the most reliable way of evaluating Agamemnon’s character in the carpet scene.